2008
DOI: 10.1192/pb.bp.107.017343
|View full text |Cite
|
Sign up to set email alerts
|

Audit of metabolic syndrome in adults prescribed clozapine in community and long-stay in-patient populations

Abstract: Aims and MethodsTo calculate the prevalence of metabolic syndrome in patients receiving clozapine in community and long-stay in-patient settings. Patients were assessed using measures specified by the Expert Panel of the US National Cholesterol Education Program.ResultsThe prevalence of the metabolic syndrome was calculated as 53% in the community groups and 11% in the in-patient group, although both sample sizes (particularly the in-patient group) were small. Women were more frequently affected than men in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…This figure is in keeping with the findings of previous surveys, ranging from 30% -54%, in community psychiatric populations (Mackin et al, 2007;Lamberti et al, 2006;Morgan et al, 2008) and up to 47% in hospitalised patients. (Correll et al, 2006) In contrast, an extensive Finnish birth cohort study estimated the prevalence of metabolic syndrome in a non-psychiatric population to be only 6%, demonstrating the significance of psychiatric illness on physical health parameters.…”
Section: Significant Findingssupporting
confidence: 80%
See 3 more Smart Citations
“…This figure is in keeping with the findings of previous surveys, ranging from 30% -54%, in community psychiatric populations (Mackin et al, 2007;Lamberti et al, 2006;Morgan et al, 2008) and up to 47% in hospitalised patients. (Correll et al, 2006) In contrast, an extensive Finnish birth cohort study estimated the prevalence of metabolic syndrome in a non-psychiatric population to be only 6%, demonstrating the significance of psychiatric illness on physical health parameters.…”
Section: Significant Findingssupporting
confidence: 80%
“…(Saari et al, 2005) Morgan's survey, also looking at psychiatric inpatients, detected a much lower rate (11%) than did our study. (Morgan et al, 2008). Although carried out on an inpatient population, this work is not directly comparable to ours as the sample were all long stay inpatients and treated with clozapine.…”
Section: Significant Findingsmentioning
confidence: 89%
See 2 more Smart Citations
“…The prevalence in our study is rather high, considering that Taiwanese are Asian (Chuang et al, 2004). A recent report showed that the prevalence of MetS in a long-stay inpatient group was 11%, which was considerably lower than that found in community groups, 53%, although the small size of the sample of inpatients (N = 11) is a limitation of that study (Morgan et al, 2008). However, the inclusion criteria were similar in that the patients were receiving clozapine for at least 3 months at the time the survey was conducted (Bai et al, 2011).…”
Section: Discussionmentioning
confidence: 93%